Evaluation of rainfall triggering landslide at Taman Hillview, Ampang Basedo on historical records of rainfall - Mohd Ishak, Syamsul Amri; Omar, Husaini; Ghazali, Abdul Halim (2008)
Rainfall induced landslides are very common, especially in the tropical country like Malaysia. Many slopes are stable under unsaturated conditions, but fail during or soon after a rainfall event. Following a long period of heavy rainfall, a catastrophic landslide occured at Taman Hillview, Ampang Selangor on the 20th November 2002. The evaluation of the rainfall triggering landslides are necessary to be implemented in an early warning system with the aim of predicting severe landslide events at this area based on historical records of rainfall. The statistical hydrological analysis on moving daily rainfall data has been carried out following Weibull probability theory and frequancy analysis. This analysis was designed to make a correlation between landslide tragedy and hydrological conditions. The frequancy analysis was used to find the actual depth of critical rainfall and its return period. Then the effect of hourly rainfall up to 24 hours and daily rainfall up to 30 days on the extent of landslides in this area was examined. Based on rainfall analysis carried out, the area around Taman Hillview experienced an exceptionally wet month with a 25 rain days from 22nd October till 20th November 2002. The total 30 days rainfall recorded prior to the tragedy during this period was 676 mm and this was 130.7% more than 293mm, the mean of monthly rainfall for November and 41.7% higher than its 30-days long-term mean of 477mm. The amount of rainfall for the month of tragedy was 537mm, which is the second highest monthly rainfall of november recorded since 1952. The minimum rainfall threshold triggering landslide reactivation on the slope was determined by examining rainfall patterns during the 30 days preceding the slide events. For the landslides at Taman Hillview, the minimum triggering threshold consists of rainfall events lasting 11 days, with cumulated rainfall exceeding 261mm.